Beyond the “estampitas”: tensions between aboriginality and holiness in Ceferino Namuncurá images (Quinto Sol, 2011)
Ceferino Namuncurá, who was beatified by the Catholic Church, is one of the most popular national saints. His indigenous origin and his studies to be a Salesian were decisive in his biography according to different historical models: the holy child, like children saints of Europe, the "santito criollo" like a national model, or the "holy Mapuche," the new model of holiness. We will analyze the images and biographies of Ceferino Namuncurá along the 20th and 21st century, to study the tension generated between aboriginality and holiness in this particular construction. In this way we intend to support the construction of discourse analysis with the iconographic analysis applied on drawings, photographs and paintings.
Keywords: Patagonia; Ceferino Namuncurá; saints; images